Pengaruh Budaya Perusahaan Terhadap Perencanaan Sumber Daya Manusia - Nisifa Prila Anisa; Elia Cahyani; Zilma Juwita (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Companies and organizations certainly have their own goals. To achieve this goal, of course, there are many series of Management Planning and Human Resource Planning (PSDM). However, HR Planning must be effective in order to achieve competitive advantage. Unfortunately, in preparing HR planning, it is necessary to adjust to the existing company culture. This is because the company culture itself contains formal values that need to be adhered to by the SDM. Therefore, the author will discuss the correlation between HR Planning and Corporate Culture in this article.